Retold stories: analysis of fashion images with afro-descendants (DAPesquisa, 2021)
With antiracial manifestations and the interest in this collective action, fashion through styling represents and instrument of expression and social reflection. This study aims to analyze the stylings of Ibrahim Kamara from the perspective of afrofuturism. The approach is necessary because it is known that stylings are created to communicate and Kamara recognizes the body with a biopolitical character, body-history, creates narratives with the protagonist of Afro-descendants in peripheral scenarios. Method addresses Gillian Rose´s visual methodology (c2016), starts with styling from the perspective of fashion photography until the case study of Kamara´s stylings arrives; and afro-descendants in fashion editorials. It is analyzed that Kamara problematizes the visual references to break aesthetically with the centralizing, normalizing and traditional power propagated by Europeanized, Americans, white and traffic views through reflections on the future of society. However, fashion visually expresses these resistance behaviors and the styling is one of the practices that contributes to an image construction of a social nature
Keywords: Fashion; Fashion editors; Image consultants; Costume designers; Kamara, Ibrahim